Pengaruh Motivasi, Inovasi, Dan Kompetensi Terhadap Keberhasilan UMKM Dengan Kemampuan Usaha Sebagai Variabel Intervening - Nurjanah Nurjanah; Sutrisno Sutrisno; Rita Meiriyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to examine and analyze the effect of motivation, innovation, and entrepreneurial competence on the success of with business ability as an intervening variable. The sample in this study was 110 respondents who were employees of Jenang Mubarokfod Cipta Delicia Kudus. The sampling technique in this study used the Probability Sampling Technique with proportional random sampling. The data analysis technique used is PLS-SEM (Partial Least Square-Structural Equation Model). The processing of this research data uses the SmartPLS 3.0 tool. Based on this research, it shows that motivation influences the success of Jenang Mubarokfood Cipta Delicia Kudus with a P-Value (0.004). Innovation has no effect on the success of Jenang Mubarokfood Cipta Delicia Kudus with a P-Value of (0,147). Entrepreneurial competence influences the success of Jenang Mubarokfood Cipta Delicia Kudus with a P-Value of (0.000). Motivation has no effect on success which is mediated by business ability in Jenang Mubarokfood Cipta Delicia Kudus with a P-Value of (0.545). Innovation has an effect on success which is mediated by business ability in the Jenang Mubarokfood Cipta Delicia Kudus with a P-Value of (0.001). Entrepreneurial competence has an effect on success which is mediated by business ability in Jenang Mubarokfood Cipta Delicia Kudus with a P-Value of (0.007).